Partial Discharge Diagnosis and Localization in Underground Cable at Hin Kong Power Station, Nong Kae District, Saraburi, Thailand - Phongsa, Adisorn; Plueksawan, Winai (Frontiers in Engineering Innovation Research, 2020)
This article presents an investigation of underground cable at Hinkong power station, Nongkae district, Saraburi province, Thailand which using Damped AC (DAC) Energizing and Conventional Partial Discharge (PD) Detection Method according to IEC 60270 and IEEE 400.3 as a regular maintenance program of Provincial Electricity Authority (PEA). The PD test has been performed over two underground power circuits in the duct bank, 12/20 kV - XLPE cable hosed in the HDPE pipe, length from switchgear to riser pole of 336 m and 368 m. The test result of the first circuit indicates the PDIV (Partial Discharge Inception Voltage) at voltage of around 17.1 kVpk (1Uo) at PD 2,250 pC which has Phase Resolved Partial Discharge (PRPD) corresponded to the characteristics of PD occurring from the internal discharged at a distance of approximately 282 m from the test location. The test result of the second circuit indicates the PDIV at the voltage of around 7.6 kVpk (0.4Uo) at PD 2,750 pC which has PRPD corresponded to the characteristics of PD occurring from the internal discharged at a distance of approximately 366 m from the test location